Desa Mitra dalam Budidaya Tanaman Obat Keluarga Menuju Desa Cibiru Wetan sebagai Sentra Herbal - Fauzan Zein Muttaqin; Widhya Aligita; Soni Muhsinin; Dadang Juanda; Aiyi Asnawi (Jurnal Pengabdian Pada Masyarakat, 2018)
PARTNER VILLAGE IN FAMILY MEDICINE PLANT CULTIVATION TOWARDS CIBIRU WETAN VILLAGE AS A HERBAL CENTER. The area of ​​Cibiru Wetan Village is a farming area because besides the limited water supply, the land is hilly. With the initiative and participation of women farmer groups which had so many achievements and skills, it was necessary to explore the potential that could provide a new icon for Cibiru Wetan Village. The purpose of the activity was to socialize and practice the cultivating of the medicinal plants carried out by a group of women farmers with simple and effective technology and finally able to become a center of dried herbs production. The method used in the cultivation program for medicinal plants was divided into three stages. The first stage was to provide material counseling on family medicinal plants including the understanding of the benefits of the plant, the second stage was to provide an explanation or training in planting family medicinal plants and the last stage or third stage was to practice directly in planting these medicinal plants. The results showed a positive understanding of both groups for both the socialization and counseling stages as well as for the practice of medicinal plants cultivation. It could be concluded, the partner village activities in medicinal plants cultivation could improve the understanding of the target group.